Debt and Destruction: The Global Abuse of Haiti and Unbalancing the Myth of Benevolent Canada - Sabrina Uwase (Caribbean Studies Students' Union, 2020)
An integral responsibility of nation-states is to provide protection and the means for attaining a fulfilling life to those it governs. Given the fact that most current global powers were not founded with the needs of racialized peoples in mind, one is infuriated but not surprised, at the cyclical pattern of disregard and exploitation that people of colour in the Americas experience. Indigenous and Black communities in the Americas are not just disregarded by the state, but are actively targeted for exploitation and undermining. Analyzing Haiti's post-colonial history and Canada's domestic and international mining operations, I argue that nations in the Caribbean and Latin America have been extensively exploited economically by imperial powers, and their survival undermined by colonial legacies. Numerous countries in the region, to varying degrees, continue to experience the wrath of state-sponsored white supremacy and crippling debt that prevent authentic development. I advance the position that coerced debt and resource extraction have been weaponized against already ostracized communities by behemoth states that employ the myth of being a post-racial democracy. This paper also highlights a complex set of global relationships by linking extraction, state-corporate relations, and North-South divides, with a focus on Canadian mining in Latin America.